Suplementação de L-carnitina na ração de matrizes suínas nulíparas e primíparas - Rhuan Filipe Chaves (2017)
The use of L-carnitine in the diet of sows is a viable alternative for the minimization of the effects caused by the hyperprolificity. This work has as main theme to compare the use of L-carnitine in gestation and / or lactation on the performance of the sow and its respective litter. Chapter 1 describes a literature review related to the research topic. The experiment was divided into two steps, both using the randomized block design. In the first stage, the inclusion or not of 125 mg/d of L-Carnitine from the six days of gestation until delivery was evaluated. The sows were distributed maintaining in each treatment the same number of animals from each parity, as well as similar body weight. Thirty four sows per treatment were used, the experimental unit was composed by the sow and its respective litter. The gestation experimental diets were: Control and L-carnitine. The second stage was conducted in the lactation phase with supplementation of 250 mg L-Carnitine in the feed from the day of farrowing until weaning (average of 20 days). The sows were distributed according to their treatment during gestation. Thus, treatments in lactation were: Control in gestation and lactation; L-carnitine in gestation and lactation; Control in gestation and L-carnitine in lactation; L-carnitine in gestation and control in lactation. For the seond phase seveteen replicates per treatment were used being the experimental unit represented by a sow and its respective litter. The sows were distributed maintaining in each treatment the same number of animals of each parity, as well as similar body weight. The variables analyzed to verify the performance were: number of liveborn piglets, stillbirths, mummified, total births, total birth weight, mean individual birth weight, coefficient of variation at birth, placental weight, placental efficiency, Feed intake of the sows during the lactation period, weight loss of sows in kg and %, milk yield kg / d, average weight of litter at weaning, average daily weight gain of litter. The use of L-carnitine in the gestation and / or lactation period of sows did not alter the performance